Dynamic Determinants of Indonesia's Economic Growth: Evidence from Energy, Investment, and Urbanization - Alvin Yunas Alfariz; Dian Octaviani; Syofriza Syofyan (Jurnal Ekonomi Pembangunan, 2026)
This study analyzes the influence of non-renewable energy consumption (NRE), renewable energy consumption (REN), CO2 emissions, Foreign Direct Investment (FDI), Gross Fixed Capital Formation (GFCF), and urbanization (URB) on Indonesia's GDP per capita. As a country still reliant on fossil fuels, Indonesia faces a dilemma between pursuing high economic growth and maintaining environmental sustainability. The study used annual time-series data from 1975 to 2024 using the ARDL approach. The results show that in the long run, GFCF has a significant positive effect on GDP per capita, confirming physical capital accumulation as the main structural driver of the Indonesian economy. Meanwhile, in the short run, NRE and FDI show a significant negative effect, and REN and CO2 show a significant positive effect. In contrast, GFCF and URB show a significant nonlinear relationship to economic growth. These findings emphasize that renewable energy transition policies need to be carefully designed so that economic growth does not sacrifice environmental sustainability, while still considering other macroeconomic variables.